Why Mozart compositions during pregnancy should be exposed in the night. Study on apoptotic index of Rattus norvegicus offsprings’ brain neurons - Eka Nasrur Maulana; Hermanto Tri Joewono; Widjiati Widjiati; Windhu Purnomo (Universitas Airlangga, 2017)
Objectives: To analyze the optimal time to expose Mozart compositions(in the night/ dark) by measuring brain neural apoptotic index of Rattus norvegicus offspringsMaterials and Methods: This study used experimental random-ized post test only control group design in pregnant Rattus norvegicus. Subjects were divided into three groups at random, ie control group, 1 (1 hour Mozart exposure in dark) and 2 (1 hour Mozart in light), each comprised 8 females. After delivery, 2 heaviest Rattus norvegicus offsprings were chosen, totally 15 neonates in each group, then they were sacrificed with decapita-tion and the brain was prepared and stained using TUNEL assay method and the index of neurons cell apoptosis was calculated using microscope in 1000x magnification. This study was conducted at the Faculty of Veterinary Medicine, University of Airlangga, after conducting ethical feasibility test.Results: There were no miscarriages, congenital malformation, preterm birth and deaths in all groups. The control group's neural apoptosis index was 55.98 ± 4.12, group one 24.87±3.45 and group two 23.82±3.89. Based on statistical test result, there was no significant difference of apoptosis index between treatment group 1 and treatment group 2, with p value 0,836 but significant difference was found between control group and treatment group 1 (p=0.002) and between control group and treatment group 2 (p=0.009). In dark group we found the lower average of apoptotic index, the lowest apoptotic index, 9 of 15 had the lowest, the heaviest head weight and 4 of 15 subjects had the heaviest head weightConclusion: There was no significant difference between the pro-vision of Mozart music in dark and light on brain neuron of Rattus norvegicus offsprings although lower average in the dark group especially if the extreme value exluded. In the dark group: we found the lower average of apoptotic index, the lowest apoptotic index, biggest proportion of the lowest index, the heaviest head and biggest proportion of heaviest head.